A study of the effect of command and task-based teaching methods on motor learning among secondary school students - idir, abdnour (sports creativity, 2025)
The purpose of the present investigation is to test 02 direct and indirect styles in teaching physical education (speed), this styles selected to find out: Effect of each of 2 styles (command, practice,) on the selected skills . 1-Hypothese: Significant differences would be existed between post and pre-test for the each of 2 styles on the acquisition of each of the selected skills in favor post test. 2-1- sample: Sample of study involve four classes from secondary schools; with a total 34 students. 2 classes we selected and distributed on the 2 styles: A- 17 students toughed by command styles. B - 17 student toughed by practice styles.